Automatic adjustment of the minimum wage: Linking the minimum wage to productivity - Oren M. Levin-Waldman (Levy Economics Institute of Bard College, 1998)
The fact that every change in the minimum wage requires an act of Congress means that debate over the wisdom of having a minimum is repeatedly returned to the political arena. As inflation continues to erode the value of the minimum wage, each legislative delay means that a larger increase is required. The larger the increase, the more resistance to its passage, so that by the time Congress acts, the political compromise is an increase that is too little and too late to be of much help in lifting workers out of poverty. Automatic adjustment of the wage, with increases keyed to measures of private sector productivity, would eliminate this problem. With the institution of a mechanism that provides regular and incremental increases, Congress will no longer be forced to revisit the issue, employers will not be confronted by sudden and large increases, and the value of the wage will be maintained.
Keywords: 330